Characterizing Marine Heatwaves in the Kerguelen Plateau Region - Su, Zimeng; Pilo, Gabriela S.; Corney, Stuart; Holbrook, Neil J.; Mori, Mao; Ziegler, Philippe (Frontiers in Marine Science, 2021)
Marine heatwaves (MHW) are periods of sustained, anomalously warm temperatures. Globally, the frequency and intensity of MHWs has been increasing in recent years, and this trend is expected to be reflected in the Kerguelen Plateau region. MHWs can negatively impact the structure of marine biodiversity, marine ecosystems, and commercial fisheries. Considering that the KP is a hot-spot for marine biodiversity, characterising MHWs and their drivers for this region is important, but has not been performed. Here, we characterise MHWs in the KP region between January 1994 and December 2016 using a combination of remotely sensed observations and output from a publicly available model hindcast simulation. We describe a strong MHW event that starts during the 2011/2012 austral summer and persists through winter, dissipating in late 2012. During the winter months, the anomalous temperature signal deepens from the surface to a depth of at least 150 m. We show that downwelling-favourable winds occur in the region during these months. At the end of 2012, as the MHW dissipates, upwelling-favourable winds prevail. We also show that the ocean temperature on the KP is significantly correlated with key modes of climate variability. Over the KP, temperature at both the ocean surface and at a depth of 150 m correlates significantly with the Indian Ocean Dipole. To the south of the KP, temperature variations are significantly correlated with the El Nino Southern Oscillation, and to both the north and south of the KP, with the Southern Annular Mode. These results suggest there may be potential predictability in ocean temperatures, and their extremes, in the KP region. Strong MHWs, like the event in 2012, may be detrimental to the unique ecosystem of this region, including economically relevant species, such as the Patagonian Toothfish.